The Anatomic Relationship of the Tibial Nerve to the Common Peroneal Nerve in the Popliteal Fossa: Implications for Selective Tibial Nerve Block in Total Knee Arthroplasty - Eric R. Silverman; Amaresh Vydyanathan; Karina Gritsenko; Naum Shaparin; Nair Singh; Sherry A. Downie; Boleslav Kosharskyy (Pain Research and Management)
Background. A recently described selective tibial nerve block at the popliteal crease presents a viable alternative to sciatic nerve block for patients undergoing total knee arthroplasty. In this two-part investigation, we describe the effects of a tibial nerve block at the popliteal crease. Methods. In embalmed cadavers, after the ultrasound-guided dye injection the dissection revealed proximal spread of dye within the paraneural sheath. Consequentially, in the clinical study twenty patients scheduled for total knee arthroplasty received the ultrasound-guided selective tibial nerve block at the popliteal crease, which also resulted in proximal spread of local anesthetic. A sensorimotor exam was performed to monitor the effect on the peroneal nerve. Results. In the cadaver study, dye was observed to spread proximal in the paraneural sheath to reach the sciatic nerve. In the clinical observational study, local anesthetic was observed to spread a mean of 4.7+1.9 (SD) cm proximal to popliteal crease. A negative correlation was found between the excess spread of local anesthetic and bifurcation distance. Conclusions. There is significant proximal spread of local anesthetic following tibial nerve block at the popliteal crease with possibility of the undesirable motor blocks of the peroneal nerve.